Suwanee Lumber Company (B) - Elias, Jaan, (SAGE Business cases., 2020)
In early 2018, Blue Wolf Capital Management received an offer to sell both its mill in Arkansas (Caddo) and its mill in Florida (Suwanee) to Conifex, an upstart Canadian lumber company. Blue Wolf hadn't planned to put both mills up for sale yet, but was the deal too good to pass up?